"I was determined to breastfeed, and I always found a solution": successful experiences of exclusive breastfeeding among Chinese mothers in Ireland - Qianling Zhou; Haoyue Chen; Katherine M. Younger; Tanya M. Cassidy; John M. Kearney (BMC, 2020)
Abstract Background The prevalence of exclusive breastfeeding for at least 4 months was previously found to be very low among Chinese immigrants in Ireland, at 5.8% (Zhou et al., Front Public Health 6:351, 2018). This study investigates the successful experiences of Chinese mothers living in Ireland who exclusively breastfeed for between four and 6 months. Methods Participants were recruited from the sample of the Ireland Chinese Mother Survey. Qualitative in-depth interviews were conducted with fourteen participants in their homes or public places. Results A content analysis revealed that various factors contributed to a successful experience of exclusive breastfeeding among the group of Chinese immigrant mothers, including strong self-determination; appropriate physical conditions; awareness of the benefits of exclusive breastfeeding; a lack of time constraints; and family, professional and policy support. The barriers that the mothers faced included the difficulty of balancing breastfeeding and employment, infant health issues, language barriers, an inability to consume the traditional Chinese postpartum diet and a lack of public breastfeeding facilities. Measures taken to overcome these barriers included seeking family support, resting during the lactation period, and pumping breast milk to feed from a bottle when outside the home. Conclusions This study highlights unique factors affecting exclusive breastfeeding among Chinese mothers in Ireland, which may be useful to health care professionals working with Chinese immigrant women internationally.